Crude glycerol by transesterification process from used cooking oils: Characterization and potentialities on hydrogen bioproduction - Rodrigues, Caroline Varella [UNESP] (2016)
This study evaluated the potential bioconversion of crude glycerol from biodiesel production, applying used cooking oil for biohydrogen production by fermentative bacteria consortia. The pretreatment of crude glycerol was made by pH adjustment. Heat treatment of the inocula and initial pH 5.5 were applied to select hydrogen-producing bacteria and inactivate hydrogen-consumers microorganisms. The inocula tested were: (I) granular sludge from the thermophilic UASB reactor used on the treatment of vinasse and (II) granular sludge from the UASB reactor used on the treatment of sanitary sludge for the assays (1) and (2), respectively. The characterization of crude glycerol presented high levels of alkalinity, methanol and soap that may be inhibitory to biologic processes of H2 production. The assays were carried in anaerobic batch reactors in order to verify the efficiencies of crude glycerol to H2 generations by the microbial consortia (20%) at 37 °C, initial pH 5.5, with 20.0 g COD L−1 glycerol. The cumulative production of hydrogen for the assays (1) and (2) were, respectively, (mmol H2 L−1) 28.49 ± 1.55 and 19.14 ± 1.67. The subsequent yields were obtained as follows: 2.2 moL H2 mol−1 glycerol and 1.1 moL H2 mol−1 glycerol, respectively. The used cooking oil was an efficient waste for bioconversion of crude glycerol to H2 production.